Iron accumulation is associated with periodontal destruction in a mouse model of HFE‐related haemochromatosis. (2nd December 2021) - Han, Pingping; Liu, Tianqing; Vaquette, Cedryck; Frazer, David; Anderson, Gregory; Ivanovski, Sašo
Abstract: Objective: To investigate the effect of Hfe gene mutation on the distribution of iron and periodontal bone loss in periodontal tissues. Background data: It remains unclear how tissue iron loading affects the periodontium architectures in a genetic animal model of hereditary haemochromatosis (HH). Methods: Male C57BL/6 Hfe −/− (8 weeks old) and wild‐type (WT) mice were utilized to examine the iron distribution in periodontal tissues, as well as periodontal tissues changes using micro‐computed tomography and histomorphometric analysis. Furthermore, tissue inflammatory mediators, bone markers and periodontal pathogens were carried out in PFA‐fixed paraffin‐embedded tissues using ELISA, RT‐qPCR and genomic DNA qPCR, respectively. Results: Excessive iron deposition was found in the periodontal ligament, gingiva and alveolar bone in Hfe −/− mice relative to their WT counterparts. This, in turn, was associated with significant periodontal bone loss, increased cemento‐enamel junction‐alveolar bone crest distance and decreased expression of molecules involved in bone development and turnover. Furthermore, the pro‐inflammatory cytokine ‐ interleukin 6 and periodontal bacteria – Campylobacter rectus were significantly increased in Hfe −/− mice compared with WT controls. Conclusion: Our results suggest that the iron loading in a mouse model of HH decreases alveolar bone formation and leads to alterations in the inflammatory state in the periodontium. Periodontal health should be assessed during the clinical assessment of HFE‐HH patients.